Quality of mineral waters as to the microbiological and physical-chemical aspects analyzed from 2017 to 2019 in the Metropolitan Region of Belém, Pa (Research, Society and Development, 2020)
The increase in pollution of water resources by countless effluents generates insecurity with society and causes a decrease in the quality of bottled mineral water and in its main consumption objective, which is health protection. However, the risk exemption for human health is only guaranteed when the microbiological parameters, chemical substances and physical properties those are in accordance with the pre-established standards in resolutions such as RDC 274 and 275 ANVISA / 2005. In this sense, this work aimed to analyze the quality of 10 brands of mineral water marketed in the Metropolitan Region of Belém in a 20L bottle as to the microbiological and physical-chemical parameters according to the current legislation. Of the 60 samples analyzed, only three marks obtained 100% satisfaction with regard to microbiological tests, and among the other brands, 25% were found with the presence of reducing sulfite Clostridium, Chromobacterium violaceum and with a higher frequency of total coliforms. Regarding the physical-chemical analyzes, it was concluded that despite the compliance with the standard established in the legislation, it is possible to point out the fragility of the water resource, whose water quality may be closely associated with the depth of the well to collect water, local environmental vulnerability, infiltration, leaching and handling in the filling procedure.